The response of axially restrained non-composite steel-concrete-steel sandwich panels due to large impact loading - Remennikov A.M.; Kong S.Y.; Uy B. (2023)
In conventional steel-concrete-steel (SCS) construction, the external steel plates are connected to the concrete infill by welded shear stud connectors. This paper describes a programme of experimental and numerical investigations on reduced-scale non-composite SCS panels with axially restrained connections. The experimental results have demonstrated that the non-composite SCS panels are capable of developing enhanced load-carrying capacity through the tensile membrane resistance of the steel faceplates. This type of construction was found to exhibit highly ductile response and be able to sustain large end rotations of up to 18 without collapse. High fidelity finite element models for SCS panels under impact loading conditions were developed and the simulation results were validated against the experimental data. With the validated FE models, a full-scale barrier structure composed of the non-composite SCS panels and steel posts was subjected to a head-on collision by the Ford F800 single unit truck. The simulation results showed that the non-composite SCS barrier construction is able to resist very large impact energy and effectively terminate the fast moving vehicle. The axially restrained non-composite SCS panels were found to provide an effective means for protecting assets against severe impact attacks. 2012 Elsevier Ltd.